Optical and Electrical Properties of TiO2/Co/TiO2 Multilayer Films Grown by DC Magnetron Sputtering - Marcos G. Valluzzi; Lucas G. Valluzzi; Marcos Meyer; María A. Hernández-Fenollosa; Laura C. Damonte (Advances in Condensed Matter Physics)
Transparent oxide multilayer films of TiO2/Co/TiO2 were grown on glass substrate by DC magnetron sputtering technique. The optical and electrical properties of these films were analyzed with the aim of substituting ITO substrate in optoelectronic devices. The samples were characterized by UV-visible spectroscopy, atomic force microscopy (AFM), and Kelvin probe force microscopy (KPFM). The effect of Co interlayer thickness (4, 8, and 12 nm) on the transmittance spectra yielded an optical absorption edge shift. The work function of these films was determined by KPFM technique allowing us to predict the Fermi level shift by extending the model for pure materials to our multilayer system. The Fermi level and optical absorption edge seem to be correlated and shifted toward lower energies when Co interlayer thickness is increased.